Is the ‘EURO’ a Defunct Currency? - ALEXIOU, Constantinos; Nellis, Joseph (International Journal of Economics and Financial Issues, 2012)
In this paper we provide a brief discourse on the theory of optimum currency areas to serve as a basis for constructive criticism of the conceptual framework of the eurozone. With particular reference to the Greek economic crisis, we argue that the very architecture of the EU experiment involving the single currency was inherently flawed from the outset in so far as political pressures to speed up the process towards a politically unified Europe has resulted in what is perceived as the worst economic impasse in the history of modern capitalism. Keywords: Optimum Currency Area; Economic and Monetary Integration; Euro; Greece. JEL Classifications: E42; F13; F33; F42